Association of Hypertensive Disorders of Pregnancy with variations in Serum Sodium and Potassium Concentration - yaqub, Umairah; Khattak, Irfan; Naseem, Samina; Imran, Ayesha; Kamal, Khawar; Niazi, Abbas (Pakistan Armed Forces Medical Journal, 2023)
Objective: To study the variation in Serum Sodium and Potassium concentration in Pre-eclampsia and Normotensive pregnant ladies.Study Design: Cross-sectional study.Place and Duration of the Study: Combined Military Hospital, Kharian District Gujrat Pakistan, from Jun 2020 to Jan 2021.Methodology: The study population Comprosed of 80 pre-eclamptic and 80 normotensive pregnant women recruited consecutively at their first, third trimester, and prenatal visits. Serum Sodium and Potassium were analysed using Ericson Photometer.Results: When the two Groups were compared, in the Normotensive Group, the mean Sodium concentration of 132±4.490 mEq/dl was significantly less than the Pre-eclampsia Group of 139.1±3.909 mEq/dl. On the contrary, mean Serum Potassium concentration was significantly less in Pre-eclampsia 3.54±0.511 mmol/L compared to the Normotensive Group to 4.0±0.513 mmol/L.Conclusion: High levels of Sodium and low level of Potassium were observed in the Pre-eclampsia Group. There may be a causal relationship between electrolyte fluctuations and Pre-eclampsia.Keywords: Electrolytes, Hypertension, Potassium, Pre-eclampsia, Sodium.